2009
DOI: 10.1002/art.25003
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of proinflammatory cytokines interleukin‐1β, interleukin‐6, and tumor necrosis factor α in mixed cryoglobulinemia

Abstract: Objective. No single previous study has evaluated serum levels of the proinflammatory cytokines interleukin-1␤ (IL-1␤), IL-6, and tumor necrosis factor ␣ (TNF␣) in patients with hepatitis C virus-associated mixed cryoglobulinemia (HCV-MC). This study was undertaken to evaluate serum levels of these cytokines in patients with HCV-MC.Methods. Serum IL-1␤, IL-6, and TNF␣ were assayed in 43 patients with HCV-MC, in 43 sex-and age-matched patients with chronic HCV without cryoglobulinemia, and in 43 sex-and age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 43 publications
2
27
0
3
Order By: Relevance
“…Several other studies have also reported increased blood levels of IL-6, -8, and -10 among patients infected with HCV (3,19,20,25,29). These cytokines appear to be critical for PBMC survival as recombinant IL-8 inhibits apoptosis of endothelial cells by enhancing the expression of antiapoptotic genes such as B cell lymphoma 2 (Bcl-2) and extra large Bcl-xL (12).…”
Section: Discussionmentioning
confidence: 98%
“…Several other studies have also reported increased blood levels of IL-6, -8, and -10 among patients infected with HCV (3,19,20,25,29). These cytokines appear to be critical for PBMC survival as recombinant IL-8 inhibits apoptosis of endothelial cells by enhancing the expression of antiapoptotic genes such as B cell lymphoma 2 (Bcl-2) and extra large Bcl-xL (12).…”
Section: Discussionmentioning
confidence: 98%
“…During the development of T1D, different cytokines are involved in inflammation. A growing body of evidence suggests that locally produced pro-inflammatory cytokines IL-b, TNF-a, and IL-6 play a critical role in the pathogenesis of inflammatory diseases (Antonelli et al, 2009). IL-10 is an immunomodulatory cytokine with potent anti-inflammatory properties (Mandal, Pritchard, & Nagy, 2010), which can decrease the production of pro-inflammatory cytokines, including TNF-a and IL-1b (O'Shea and Murray, 2008).…”
Section: Effects Of Lpps Administrations On Th1 and Th2 Cytokines Secmentioning
confidence: 99%
“…A growing body of support advises that locally produced proinflammatory cytokines TNF-a and IL-6 play a critical role in the pathogenesis of inflammatory diseases (Antonelli et al, 2009). In contrast, IL-10 is an immuno-modulatory cytokine with potent anti-inflammatory properties (Mandal, Pritchard, & Nagy, 2010), which can decrease the production of pro-inflammatory cytokines, including TNF-a and IL-6 (O'Shea & Murray, 2008).…”
Section: Discussionmentioning
confidence: 98%